Antibiotic susceptibility pattern of bacteria in patients with middle ear infection - Lalbibi; Taj, Muhammad Kamran; Azam, Saima; Khan, Sakina (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the antibiotic resistance profiles of bacterial pathogens isolated from patients with middle ear infections. Method: The cross-sectional study was conducted at the Centre for Advanced Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta, Pakistan, from November 2022 to December 2023, and comprised swab samples from middle ear infections collected from the Bolan Medical Complex Hospital, Quetta. The samples were promptly cultured, and positive cultures underwent biochemical tests, antibiotic susceptibility testing, and polymerase chain reaction analysis. Data was analysed using SPSS 22. Results: Of 1,000 samples, 788 (78.8%) tested positive for pathogenic bacteria; 404 (40.4%) from male patients, 384 (38.4%) from female patients, and 474 (47.4%) from patients aged 1-15 years. Pseudomonas aeruginosa was the most prevalent bacterium 192 (24.3%), followed by staphylococcus aureus 154 (19.5%), escherichia coli 99 (12.5%), klebsiella pneumonia 107 (13.5%) and clostridium perfringens 71 (9%). Demographic analysis revealed a higher incidence among males 404 (40.4%) compared to females 384 (38.4%), with illiterate individuals being significantly more affected 568 (56.8%) than literate individuals 220 (22%). Socioeconomic factors also influenced infection rates, with more cases in those having a lower class 544 (54.4%). Infections were observed in all age groups, with the highest prevalence in individuals aged 1-15 years 474 (47.4%). Polymerase chain reaction analysis confirmed the bacterial presence, identifying specific gene bands for each organism. All isolates showed high resistance to metronidazole, tetracycline, lincomycin, and penicillin G. Conclusion: Middle ear infections were most prevalent in patients aged 1-15 years. The bacterial isolates demonstrated multidrug resistance, highlighting the importance of enhancing efforts to isolate microorganisms and determine their susceptibility patterns in order to improve the treatment outcomes for otitis media. Key Words: Antibiotic resistance, Bacterial profiling, Otitis media.